Enhancing Cognitive Functioning in Healthly Older Adults: a Systematic Review of the Clinical Significance of Commercially Available Computerized Cognitive Training in Preventing Cognitive Decline - Shah, T.; Weinborn, M.; Verdile, Giuseppe; Sohrabi, H.; Martins, R. (Springer, 2017)
Successfully assisting older adults to maintain or improve cognitive function, particularly when they are dealing with neurodegenerative disorders such as Alzheimer’s disease (AD), remains a major challenge. Cognitive training may stimulate neuroplasticity thereby increasing cognitive and brain reserve. Commercial brain training programs are computerized, readily-available, easy-to-administer and adaptive but often lack supportive data and their clinical validation literature has not been previously reviewed. Therefore, in this review, we report the characteristics of commercially available brain training programs, critically assess the number and quality of studies evaluating the empirical evidence of these programs for promoting brain health in healthy older adults, and discuss underlying causal mechanisms. We searched PubMed, Google Scholar and each program’s website for relevant studies reporting the effects of computerized cognitive training on cognitively healthy older adults. The evidence for each program was assessed via the number and quality (PEDro score) of studies, including Randomized Control Trials (RCTs). Programs with clinical studies were subsequently classified as possessing Level I, II or III evidence. Out of 18 identified programs, 7 programs were investigated in 26 studies including follow-ups. Two programs were identified as possessing Level I evidence, three programs demonstrated Level II evidence and an additional two programs demonstrated Level III evidence. Overall, studies showed generally high methodological quality (average PEDro score = 7.05). Although caution must be taken regarding any potential bias due to selective reporting, current evidence supports that at least some commercially available computerized brain training products can assist in promoting healthy brain aging.